Risk factors and relationship between screening periodicity and risk of cervical cancer among nurses and midwives: A cross-sectional study - Yörük, Selda; Açıkgöz, Ayla; Türkmen, Hülya; Ergör, Gül (São Paulo Medical Journal, 2019)
BACKGROUND: If nurses and midwives undergo cervical cancer screening regularly, they can become role models for other women regarding this screening. OBJECTIVES: The aims here were (i) to determine factors associated with undergoing cervical cancer screening; and (ii) to examine the association of cervical cancer screening periodicity with cervical cancer risk levels among nurses and midwives. DESIGN AND SETTING: Cross-sectional study in a public hospital. METHODS: 466 nurses and midwives participated in this study. The relationships between undergoing Pap smear screening and sociodemographic characteristics, cervical cancer risk factors, perception of cer-vical cancer risk and calculated cervical cancer risk levels were examined. Cervical cancer risk levels were determined using the “Your Disease Risk” assessment tool (Washington University). RESULTS: 35% of the nurses and midwives had undergone Pap smear testing at least once in their lifetimes. The odds of having undergone Pap smear testing were higher among smokers (odds ratio, OR: 2.08; 95% confidence interval, CI: 1.24-3.48) and among those who perceived their risk of cervical cancer to be high (OR: 3.60; 95% CI: 1.36-9.51). The frequency of undergoing Pap smear testing at least once in a lifetime was higher among primiparae (OR: 17.99; 95% CI: 6.36-50.84) and secundiparae (OR: 41.53; 95% CI: 15.01-114.91) than among nulliparae. No relationship was found between Pap smear test periodicity and calculated risk level. CONCLUSION: There is a need to assess motivational barriers that might lead to low levels of Pap smear screening among nurses and midwives who are role models for women regarding cervical cancer prevention.